1987
DOI: 10.1111/j.1095-8649.1987.tb05241.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the spawning migrations of brown trout, Salmo trutta L., and rainbow trout, S. gairdneri Richardson, in Great Lake, Tasmania

Abstract: Upstream spawning migrations of mature brown trout, S. truIIu, and rainbow trout. S. gairdneri, werestudied in LiaweneeCanal, Great Lake from 1949 to 1985. Brown trout migrations normally occurred from early April to mid-May and rainbow trout from late August to early November. In 1983.16 425 brown trout and I338 rainbow trout passed through a fixed upstream diversion trap. Brown trout spawning migrations occurred predominantly over the temperature range 6 1 0 " C, while rainbow trout migrated predominantly ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The spawning run of trout is influenced by increased water flow, but sometimes water temperature or a combination between flow and temperature appears important. For instance, in Great Lake, Tasmania, the spawning migration occurred predominantly at low flow when the temperature was 6–10 °C, with peak migration at 7.6 °C (males) and 7.8 °C (females) (Davies & Sloane 1987). Ovidio et al.…”
Section: Brown Trout Salmo Trutta Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The spawning run of trout is influenced by increased water flow, but sometimes water temperature or a combination between flow and temperature appears important. For instance, in Great Lake, Tasmania, the spawning migration occurred predominantly at low flow when the temperature was 6–10 °C, with peak migration at 7.6 °C (males) and 7.8 °C (females) (Davies & Sloane 1987). Ovidio et al.…”
Section: Brown Trout Salmo Trutta Lmentioning
confidence: 99%
“…The spawning run of trout is influenced by increased water flow, but sometimes water temperature or a combination between flow and temperature appears important. For instance, in Great Lake, Tasmania, the spawning migration occurred predominantly at low flow when the temperature was 6-10 8C, with peak migration at 7.6 8C (males) and 7.8 8C (females) (Davies & Sloane 1987). Ovidio et al (1998) radio-tagged brown trout in the Belgian Ardennes and found that a combination of high variations of water temperature and water level between consecutive days within a thermal range of 10-12 8C triggered the upstream migration.…”
Section: Migration and Habitat Shiftsmentioning
confidence: 99%
“…Barometric pressure and lunar cycles may also stimulate migration (Peterson 1972;Grau 1981;Davies & Sloane 1987). Some of these factors are interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…Day length, water temperature, and river flow vary together in seasonal cycles and changes in barometric pressure reflect the passage of low pressure events or fronts that cause flow changes. Flow and barometric pressure are most frequently mentioned as factors controlling the rate of upstream migration in salmonids (Banks 1969;Dodge & MacCrimmon 1971;Davies & Sloane 1987;Jonsson 1991). The inter-relationship between these two variables makes it difficult to determine whether fish respond to pressure, flow, or both.…”
Section: Introductionmentioning
confidence: 99%
“…For the explanation of flow impacts on migrations and/or local movements of cyprinids, some examples of the relationship between flow and spawning migrations of salmonid fish that are locally dependent were adopted (Jonsson 1991). According to some authors (Solomon & Templeton 1976;Davis & Sloane 1987;Svendsen et al 2004), high flows positively correlated with the intensity and distance of salmonid migrations, probably in a consequence of better orientation and improved local conditions for overcoming obstacles (Jonsson 1991;Jensen & Aass 1995). Controversially, other authors reported descending migratory intensity of salmonids during high flows (Stuart 1953;Milner et al 1979;Evans 1994).…”
Section: Discussionmentioning
confidence: 99%